A puzzle-based sequencing system for logistics items - Raji Alahmad; Kazuo Ishii (Logistics, 2021)
Background: The new demands of the current market including for space should be satisfied by designing modern material flow systems. Designing warehouses using effective material handling equipment significantly supports cost reduction and efficient space utilization. Sequencing of items is an important process that leads to enhanced logistics operations. Current approaches are not capable of fully fulfilling dynamic changes. Methods: In this paper, a puzzle-based sequencing system with a high density and highly efficient floor space utilization was successfully developed. Accordingly, two solving methods were investigated: game tree and pathfinding algorithms. A-star was chosen based on pathfinding algorithms in order to find the shortest solution of the puzzle in which the sequencing time was decreased. The pre-sorting strategy was proposed to overcome the unsolvable configuration issue that cannot be solved by the aforementioned methods. Moreover, the shape of the puzzle was considered. Results: Based on numerical calculations, we found that a square shape was better than a rectangle in terms of solution steps, and we confirmed the direct relationship between the aspect ratio and rectilinear distance, which directly affects the pre-sorting steps. Conclusion: Our results prove that the puzzle-based sequencing system should be highly preferred for effective floor space utilization compared to the current systems.
Keywords: 650; 8-puzzle; A-star algorithm; sequencing